REDECA Framework Enhancing Occupational Safety and Health Through Artificial Intelligence Applications - Sheila Michiel; Isabelle Moissact; Christopher Sean (Inovasi Analisis Data, 2024)
Objective: This paper aims to show how REDECA Reengineering Delphi and Evaluation can be integrated with Artificial Intelligence (AI) in a way to increase the influence of AI on Occupational Safety and Health (OSH) by further advancing the risk identification process, the prevention of injuries, and the compliance with safety standards.Methods: A quantitative cross-sectional study method was used through multiple regressions analysis for the relationships between AI application, risk identification, injury reduction, safety culture, and compliance. Organizational safety culture was explored further as a moderator influencing the effectiveness of AI in OSH systems.Results: AI enhances the identification and prediction of risk, resulting in a significant reduction in workplace injuries and fatalities. AI-enabled applications ensure higher adherence to safety protocols and helped in building a time-tested safety culture. In fact, organizational safety culture improves the effectiveness of AI, serving as a vital moderating factor that facilitates lasting advancements in workplace safety practices. This points to the relationship between technological innovation and organizational influences on better OSH outcomes.Novelty: This study presents an original integration of AI-driven predictive safety mechanisms through the REDECA framework, highlighting the moderating role of safety culture. This serves as a bridge between technology adoption and organizational behavior to advance workplace safety strategies.Research Implication: The findings provide a roadmap to organizations to not just invest in AI-based safety systems but also to inculcate a strong safety culture to reap the rewards of technical advances. This research sends a message to the fostering of the AI integration as a transformative approach for OSH management, which aims for the sustainable improvements in workplace safety, risk mitigation and employed well-being for the policymakers and the industry leaders.